2012
DOI: 10.1039/c1cs15148g
|View full text |Cite
|
Sign up to set email alerts
|

Lyotropic liquid crystal engineering–ordered nanostructured small molecule amphiphileself-assembly materials by design

Abstract: Future nanoscale soft matter design will be guided to a large extent by the teachings of amphiphile (lipid or surfactant) self-assembly. Ordered nanostructured lyotropic liquid crystalline mesophases may form in select mixtures of amphiphile and solvent. To reproducibly engineer the low energy amphiphile self-assembly of materials for the future, we must first learn the design principles. In this critical review we discuss the evolution of these design rules and in particular discuss recent key findings regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
217
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 296 publications
(226 citation statements)
references
References 210 publications
(350 reference statements)
8
217
0
1
Order By: Relevance
“…Whilst ethanolamide-based amphiphiles are biologically relevant and have a range of commercial uses, particularly in the detergent and cosmetics industries, their physico-chemical behavior had, to date, remained poorly characterized. We have shown that small alterations to molecular structures can be used to design tailor-made amphiphiles with predictable phase behavior for specific applications such as drug delivery, cosmetic formulations, or household detergents [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst ethanolamide-based amphiphiles are biologically relevant and have a range of commercial uses, particularly in the detergent and cosmetics industries, their physico-chemical behavior had, to date, remained poorly characterized. We have shown that small alterations to molecular structures can be used to design tailor-made amphiphiles with predictable phase behavior for specific applications such as drug delivery, cosmetic formulations, or household detergents [38].…”
Section: Discussionmentioning
confidence: 99%
“…As temperature increases, an increase in chain splay leads to a more cylindrical effective geometry and fluid lamellar phase formation. Furthermore, H-bond strength plays an important role in an amphiphiles ability to form inverse liquid crystalline phases such as the inverse hexagonal (H II ) and inverse cubic phases [26,29,32,37,38]. Strong, bifurcated H-bonding in the urea moiety dominates the lyotropic phase behavior of saturated urea amphiphiles resulting in extremely high curvature amphiphiles, which are only capable of forming an L 2 phase at high temperatures and hydration [28,30].…”
Section: Structure-property Correlationsmentioning
confidence: 99%
“…Molecular self-assembly has been widely utilized to create nanostructured soft matter for applications in biomedicine as well as in electronics and optics. [1][2][3][4][5][6] In stimulus-responsive materials, molecular ordering can give rise to novel modes of activity. For example, the photoisomerization of azobenzene (AZO) motifs is used to generate dimension changes within aligned liquid crystalline (LC) networks.…”
Section: Introductionmentioning
confidence: 99%
“…The crystallographic space group of this structure is P2 1 [23][24][25][26]. They consist of a lipid bilayer draped across a periodic minimal surface of zero mean curvature (figure 2 [27,28] grown in meso have been found to be robust and of high quality and TMPs crystallized within a lipidic cubic phase are more likely to retain their activity [30]. For in meso crystallization, monoolein (MO) is the most commonly used lipid to date [5,7,31].…”
Section: Introductionmentioning
confidence: 98%